Study Design and Results of a Population-Based Study on Perceived Stress Following Hurricane Sandy. (2nd December 2015) - Schwartz, Rebecca; Liu, Bian; Sison, Cristina; Kerath, Samantha M.; Breil, Trista; Murphy, Lisa; Taioli, Emanuela
Abstract: Objective: Hurricane Sandy was one of the deadliest storms in US history, with at least 162 deaths and numerous injuries. This research aimed to quantify the impact of Hurricane Sandy on the New York metropolitan area. Methods: The project included 601 volunteers aged at least 18 years who were recruited in Nassau, Suffolk, Queens, and Richmond counties and Staten Island between 2013 and 2014 through close partnerships with coalition community leaders. Participants completed a self-administered questionnaire on demographics and behavioral factors and a 35-point check off list on hurricane exposure. Perceived stress was assessed by using the 10-item Perceived Stress Scale (PSS). Results: Participants had a mean stress score of 15.6 (SD=7.3; vs general population mean of 13.0), with 30.14% of the sample categorized as "high stress" (mean≥20). In the multivariable regression analysis, age was significantly negatively associated with PSS score. A reported history of mental health issues, Hispanic ethnicity, and overall exposure to Hurricane Sandy were statistically significantly associated with PSS score in a positive direction. Conclusions: Perceived stress was high in areas affected by Hurricane Sandy and was significantly associated with individual hurricane exposure. This study is a first step toward defining what segments of the population are more vulnerable and informing intervention and emergency preparedness efforts. ( Disaster Med Public Health Preparedness . 2015;10:325–332)